Multi-level optimization strategy for load shedding with tracing capability index - Verayiah R.; Mohamed A.; Shareef H.; Abidin I.H.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computation theory; Control systems; Electric power plant loads; Particle swarm optimization (PSO); Stability; System stability; Voltage control; Voltage stabilizing circuits; Capability indices; Load shedding scheme; Load-shedding; Location selection; Multilevel optimization; Optimization analysis; Under voltage load shedding; Voltage stability assessment; Electric load shedding